2001
DOI: 10.1016/s0005-2736(01)00328-5
|View full text |Cite
|
Sign up to set email alerts
|

Na+-coupled transport of l-carnitine via high-affinity carnitine transporter OCTN2 and its subcellular localization in kidney

Abstract: The mechanism of Na(+)-dependent transport of L-carnitine via the carnitine/organic cation transporter OCTN2 and the subcellular localization of OCTN2 in kidney were studied. Using plasma membrane vesicles prepared from HEK293 cells that were stably transfected with human OCTN2, transport of L-carnitine via human OCTN2 was characterized. Uptake of L-[(3)H]carnitine by the OCTN2-expressing membrane vesicles was significantly increased in the presence of an inwardly directed Na(+) gradient, with an overshoot, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
103
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 30 publications
6
103
0
Order By: Relevance
“…2) (Tamai et al, 1998;Tokuhiro et al, 2003;Lahjouji et al, 2004;Garrett et al, 2008). Octn2 and OCTN2 proteins are present on the brush border membrane vesicles from kidneys (Tamai et al, 2001a), placental syncytiotrophoblasts , and small intestine enterocytes , as well as the basolateral surface of epididymal cells (Rodríguez et al, 2002) (Table 4).…”
Section: Oatp1a2mentioning
confidence: 99%
“…2) (Tamai et al, 1998;Tokuhiro et al, 2003;Lahjouji et al, 2004;Garrett et al, 2008). Octn2 and OCTN2 proteins are present on the brush border membrane vesicles from kidneys (Tamai et al, 2001a), placental syncytiotrophoblasts , and small intestine enterocytes , as well as the basolateral surface of epididymal cells (Rodríguez et al, 2002) (Table 4).…”
Section: Oatp1a2mentioning
confidence: 99%
“…Loss of carnitine from the body is minimized by the Na + -dependent high affinity carnitine transporter OCTN2, which is primarily responsible for reabsorption of filtered carnitine in the kidney [5][6][7][8]. The importance of this carnitine transporter becomes apparent from the severe consequences of OCTN2-related disorders.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] OCTN2 (SLC22A5) is an Na ϩ -dependent, high-affinity (K m ϭ4 to 25 mM) carnitine transporter, 2,3) which serves to maintain carnitine levels in serum by functioning as a reabsorption transporter of carnitine after glomerular filtration. [4][5][6] It was reported that human and mouse OCTN1 transported carnitine, 1,7) whereas rat OCTN1 did not. 8) Human carnitine transporter CT2 and mouse OCTN3, which are present selectively in male reproductive tissues, 3,9) transport carnitine with high affinity (K m ϭ20 mM and 3 mM, respectively) in an Na ϩ -independent manner.…”
mentioning
confidence: 98%